A systematic analysis of nuclear charge radii data - Mamaloukas, Patroklos-Miltiadis; Mertzimekis, Theo J. (HNPS Advances in Nuclear Physics, 2019)
Driven by the need to describe strong nuclear interactions between hadrons in a nucleus, we take a closer look at evaluated experimental data of nuclear charge radii acquired mainly with laser spectroscopy methods. Understanding the range at which the components of the nucleus interact with each other shall lead to even more accurate models of nuclear potentials, and even understanding limitations of fundamental symmetries. The present work takes advantage of the existing IAEA database by Angeli & Marinova, and an additional set of recently surveyed measurements, specifically between 2013–2018. Statistical treatment includes different polynomial fits for the entirety of the data set with the intention of confirming or improving the well-established empirical formula, R=roA1/3. Various trends of observed deviations from this formula are investigated in terms of structure effects spanning major shells and near magic numbers.